Law of agency the legal rights and doties, obligations and liabilities of an agent towards principal and third party / Norlida Jamaludin - Jamaludin, Norlida (Faculty of Law, 1987)
The law of agency deals with the relationship that arise when one person is used by another to perform certain tasks on his behalf. The word agency in a general way signifies the relations that arises way to create problems of many kinds in respect of the rights and duties, resulting from the introduction of a third person. In other words there are three parties in an agency relationship, that is the party who authorizes another to do some business, the authorized party and the party with who m the business is transacted. It is meant to indicate that although there may be many situations in which one person r e presents or acts on behalf of another, it is only when such representation or action on another's behalf affects the latter's legal position, that is to say his rights against, and liabilities towards other people, that the law of agency applies. The law of agency has no relevance to social or other non-legal obligations .